Interregional and intermunicipal cooperation in the socio-humanitarian sphere with the countries of the Eurasian space - Maliutin, Nikita S. (Journal of the Belarusian State University. Law, 2026)
This article analyses the problems of intermunicipal cooperation in the geopolitical space of Eurasia in the socio-humanitarian sphere. The special role of such paradiplomacy is noted on the scale of space united by common historical and civilisational characteristics, which makes it possible to identify patterns of development in this area in individual states and to form similar approaches to their regulation. Meanwhile, a number of problems in the development of such cooperation are noted, which can be resolved through a comprehensive impact on the designated relations. As elements of such an impact, the article examines specific proposals within the framework of normative, institutional and organisational approaches aimed at developing intermunicipal and interregional cooperation in the socio-humanitarian sphere.
Keywords: inter-municipal cooperation; Commonwealth of Independent States; cultural sphere